Systematic overview of cost–effectiveness thresholds in ten countries across four continents. (September 2015) - Schwarzer, Ruth; Rochau, Ursula; Saverno, Kim; Jahn, Beate; Bornschein, Bernhard; Muehlberger, Nikolai; Flatscher-Thoeni, Magdalena; Schnell-Inderst, Petra; Sroczynski, Gaby; Lackner, Martina; Schall, Imke; Hebborn, Ansgar; et al.
Aim: To provide an overview of thresholds for incremental cost–effectiveness ratios (ICERs) representing willingness-to-pay (WTP) across multiple countries and insights into exemptions pertaining to the ICER (e.g., cancer). To compare ICER thresholds to individual country's estimated ability-to-pay.Materials & methods: We included AHRQ/USA, BIQG-GOEG/Austria, CADTH/Canada, DAHTA@DIMDI/Germany, DECIT-CGATS/Brazil, HAS/France, HITAP/Thailand, IQWiG/Germany, LBI-HTA/Austria, MSAC/Australia, NICE/England/Wales and SBU/Sweden. ICER thresholds were derived from systematic literature/website search/expert surveys. WTP was compared with ATP using Spearman's rank correlation.Results: Two general and explicitly acknowledged thresholds (England/Wales, Thailand), implicit thresholds in six countries and different ICER thresholds/decision-making rules in oncology were identified. Correlation between WTP and ability-to-pay was moderate.Discussion: Our overview supports country-specific discussions on WTP and on how to define value(s) within societies.